Finite dimensional estimation algebras with state dimension 3 and rank 2, Mitter conjecture. Issue 9 (1st September 2020) - Shi, Ji; Yau, Stephen S. T.
ABSTRACT: In this paper, we study the structure of finite dimensional estimation algebras with state dimension 3 and rank 2 arising from a nonlinear filtering system by using the theories of the Euler operator and under-determined partial differential equations. It is proved that if the estimation algebra contains a degree two polynomial, then the Wong Ω-matrix must be a constant matrix. Moreover, all functions in the estimation algebra must be linear functions.